IBM Cognos 10 Framework Manager : a comprehensive, practical guide to using this essential tool for modeling your data for use with IBM Cognos Business Intelligence Reporting /: a comprehensive, practical guide to using this essential tool for modeling your data for use with IBM Cognos Business Intelligence Reporting. (2013) - Curran, Terry
No abstract available